2024
DOI: 10.1017/langcog.2024.19
|View full text |Cite
|
Sign up to set email alerts
|

The organization of semantic associations between senses in language

Jorge A. Alvarado,
Carlos Velasco,
Alejandro Salgado

Abstract: Distributional semantic representations were used to investigate crossmodal correspondences within language, offering a comprehensive analysis of how sensory experiences interconnect in linguistic constructs. By computing semantic proximity between words from different sensory modalities, a crossmodal semantic network was constructed, providing a general view of crossmodal correspondences in the English language. Community detection techniques were applied to unveil domains of experience where crossmodal corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 110 publications
1
2
0
Order By: Relevance
“…Our results contribute to the literature on crossmodal associations, which has established that individuals link features of sensory stimuli across modalities (Alvarado et al, 2023;Motoki et al, 2024;Spence, 2011) (Förster et al, 2007), which would lead to assimilation effects-for example, warm temperatures increasing the desire for products associated with warmth. We find the opposite in our studies.…”
Section: Theoretical Implicationssupporting
confidence: 67%
See 2 more Smart Citations
“…Our results contribute to the literature on crossmodal associations, which has established that individuals link features of sensory stimuli across modalities (Alvarado et al, 2023;Motoki et al, 2024;Spence, 2011) (Förster et al, 2007), which would lead to assimilation effects-for example, warm temperatures increasing the desire for products associated with warmth. We find the opposite in our studies.…”
Section: Theoretical Implicationssupporting
confidence: 67%
“…for different senses, many experiences are multisensory by nature, requiring the integration of sensory inputs for perception and decision-making (Driver & Spence, 2000;Senkowski et al, 2008). In line with this integrative view of sensory perception, research has demonstrated that individuals often associate sensory information across the senses (Alvarado et al, 2023;Motoki et al, 2024). In a phenomenon known as crossmodal correspondence (Spence, 2011), individuals systematically link features in one sensory modality with features in other sensory modalities.…”
Section: Crossmodal Associationsmentioning
confidence: 98%
See 1 more Smart Citation